Impact of SARS-CoV2 infection on anti-apolipoprotein A-1 IgG response in inflammatory rheumatic diseases - Lamacchia, Celine; Mongin, Denis; Juillard, Catherine; Antinori-Malaspina, Paola; Gabay, Cem; Finckh, Axel; Pagano, Sabrina; Vuilleumier, Nicolas (Frontiers in Immunology, 2023)
Objectives To investigate the impact of severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) infection on anti-apolipoprotein A-1 IgG (AAA1) humoral response in immunosuppressed inflammatory rheumatic diseases (IRD) patients. Methods This is a nested cohort study from the prospective Swiss Clinical Quality Management registry. A total of 368 IRD patients for which serum samples were available before and after the SARS-CoV2 pandemic were included. Autoantibodies against ApoA-1 (AAA1) and its c-terminal region (AF3L1) were measured in both samples. The exposure of interest was anti-SARS-CoV2 spike subunit 1 (S1) seropositivity measured in the second sample. The effect of SARS-CoV2 infection (anti-S1 seropositivity) on becoming AAA1 or AF3L1 positive and on the change of AAA1 or AF3L1 optical density (OD) between the two samples was tested with multivariable regressions. Results There were 12 out of 368 IRD patients who were seroconverted against S1. The proportion of patients becoming AF3L1 seropositive was significantly higher in anti-S1-positive patients, compared with anti-S1-negative patients (66.7% versus 21.6%, p = 0.001). Adjusted logistic regression analyses indicated that anti-S1 seroconversion was associated with a sevenfold increased risk of AFL1 seropositivity (odds ratio: 7.4, 95% confidence interval (95% CI): 2.1–25.9) and predicted median increase in AF3L1 OD values (+0.17, 95% CI: 0.08–0.26). Conclusions SARS-CoV2 infection is associated with a marked humoral response against the immunodominant c-terminal region of ApoA-1 in IRD patients. The possible clinical impact of AAA1 and AF3L1 antibodies on disease progression, cardiovascular complications, or long COVID syndrome deserves future investigations.